A Tunable Ferrofluid-based Polydimethylsiloxane (PDMS) Microchannel Inductor for Ultra High Frequency Applications - Ahmad Hafiz Mohamad Razy; Mohd Tafir Mustaffa; Asrulnizam Abd Manaf; Norlaili Mohd Noh (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this work, a tunable ferrofluid-based polydimethylsiloxane (PDMS) microchannel inductor with high quality factor and high tuning range is proposed. For this project, PDMS is used to create a microchannel with a width and height of 0.53 mm and 0.2 mm respectively. The microchannel is then used to cover the whole design of a solenoid inductor. A solenoid inductor is designed using wire bonding technique where lines of copper and bond wires are used to form a solenoid winding on top of silicon substrate. A light hydrocarbon based ferrofluid EMG 901 660 mT with high permeability of 5.4 is used. The ferrofluid-based liquid is injected into the channel to enhance the performance of a quality factor. A 3D full-wave electromagnetic fields tool, ANSYS HFSS is used in this work to simulate the solenoid inductor. The results obtained in this work gives a quality factor of more than 10 at a frequency range of 300 MHz to 3.3 GHz (Ultra High Frequency range). The highest quality factor is 37 which occurs at a frequency of 1.5 GHz, provides a high tuning range of 112%.